Assessment Of Thermal Comfort In Naturally Ventilated Classrooms In The Tropical Savanna Climate Of Nigeria - Mustapha, Tajudeen Dele (2023)
Issues of climate change and energy efficiency in buildings have made thermal comfort research increasingly significant. The rising temperature caused by climate change impacts building occupants' comfort level and health, especially school children exposed to unfavourable indoor thermal conditions. Therefore, this study aims to investigate students' perceptions of the indoor thermal environment and determine the optimum thermal condition in naturally ventilated classrooms in the tropical savanna climate of Abuja, Nigeria. In achieving this aim, two field investigations and building simulations were conducted to evaluate the occupants' thermal comfort and perceptions, involving 2758 respondents from 83 classrooms during the dry and wet seasons. The respondents encompass a total of 2,739 secondary school students and 19 teachers selected from four (4) secondary schools in Abuja. The selected case studies represented a range of users in an equally comparable climatic environment with Abuja. The data collected in the surveys were fieldwork measurements, simulation of thermal comfort variables, and questionnaire answers of occupants' perceptions of the indoor climate. Accordingly, the data were stored in a spreadsheet and subjected to descriptive and inferential statistical analysis using the analytical software programs SPSS version 23 and Microsoft Excel. The assessment revealed that only 27.3% of the case-studied classrooms and 21.9% of the occupants meet the ASHRAE Standard 55 thermal comfort criteria stipulated by the American Society of Heating.